6-n-proprylthiouracil (PROP) Tasting - Plymale, Reagan; Baldwin, Anne (Valdosta, GA: Valdosta State University, 2016)
6-n-proprylthiouracil (PROP) tasting. Reagan Plymale and Anne Baldwin. Valdosta State University Undergraduate Symposium Posters, 2016.
Keywords: Posters; College students--Research; Microsoft PowerPoint (Computer file); Undergraduates